Synthesis, Characterization and Biological Screening of Novel Metal(II) Complexes of 2-{[2-(5-Benzoyl-1H-benzotriazol-1-yl)-2-oxoethyl]amino}-5-bromobenzoic Acid - Desai, P.S.; Parekh, D.V. (Asian Journal of Chemistry, 2021)
In this work, 5-bromoanthranilic acid was condensed with 1-(5-benzoyl-1H-1,2,3-benzotriazole-1-yl)-2-chloro-ethanone to form 2-{[2-(5-benzoyl-1H-benzotriazol-1-yl)-2-oxoethyl]amino}-5-bromobenzoic acid. The newly synthesized ligand and its metal(II) complexes with first transition metal series (Cu(II), Ni(II), Co(II), Zn(II) and Mn(II)) have been synthesized and characterized by using elemental analysis, infrared and electronic spectra. The IR spectra, NMR spectra and atomic absorption analysis show that the benzotriazole ligand formed chelates with metal in a 2:1 (ligand:metal) stochiometry. All the metal(II) complexes were screened for their antibacterial activity against Gram-positive and Gram-negative bacteria. Among the synthesized metal(II) complexes, Cu(II) complex showed the highest antibacterial activity.